Severe hypercalcemia as a result of disseminated Candida krusei infection - Amenah Alghamdi; Torrance Oravec; Cesilia Nishi; Eric Eckbo; Krista Marcon; Alissa Wright; Allison Mah; Jennifer White; Tom Nevill; Sara Belga (International Journal of Infectious Diseases, 2024)
Candida krusei disseminated infection is a rare complication of protracted neutropenia. Herein, we report a case of a 31-year-old male with relapsed acute myeloid leukemia who developed Candida krusei fungemia with cutaneous, ocular, splenic, renal, bone marrow and osseous involvement leading to severe hypercalcemia, treated with parenteral antifungals followed by oral ibrexafungerp.